2013
DOI: 10.1590/s0006-87052013000200012
|View full text |Cite
|
Sign up to set email alerts
|

Análise de zonas homogêneas em séries temporais de precipitação no Estado da Bahia

Abstract: ResumoO objetivo deste trabalho foi identificar zonas pluviometricamente homogêneas no Estado da Bahia e analisar as condições climá-ticas de cada zona entre 1981 e 2010. Foi aplicada a técnica de mineração de dados, Clusterização (agrupamento de dados), por meio do uso do algoritmo k-means, para transformação das séries históricas de precipitação em cinco zonas pluviometricamente homogêneas, em resposta à orografia, maritimidade e sistemas meteorológicos atuantes na região. Foram utilizados dados de médias me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
12
0
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 9 publications
4
12
0
11
Order By: Relevance
“…However, analyzing Figures 2, 9 and 10 together, the South, the Southwest and the coastal region of the state became better represented by the mesoregions defined by the authors of that article, mainly on the aspect of the annual total precipitation. Dourado et al (2013) also defined a sectorization of the State of Bahia, also under the aspect of the annual total precipitation. The study defined five groups, half of the proposed quantity by that research.…”
Section: New Clusters Proposedmentioning
confidence: 99%
See 1 more Smart Citation
“…However, analyzing Figures 2, 9 and 10 together, the South, the Southwest and the coastal region of the state became better represented by the mesoregions defined by the authors of that article, mainly on the aspect of the annual total precipitation. Dourado et al (2013) also defined a sectorization of the State of Bahia, also under the aspect of the annual total precipitation. The study defined five groups, half of the proposed quantity by that research.…”
Section: New Clusters Proposedmentioning
confidence: 99%
“…Nine sub-regions were proposed, as can be seen in Figure 2. Dourado et al (2013) used 92 pluviometric stations with a historical series of 30 years to identify homogeneous pluviometric zones, applying the data-mining technique. The k-means algorithm was used, which is also based on cluster analysis of the stations monthly data.…”
Section: Introductionmentioning
confidence: 99%
“…Among data mining techniques, clustering uses rainfall time series to define homogeneous rainfall zones, in which each rainfall station corresponds to a data time series, and a homogeneous zone is formed by grouping similar time Engenharia Agrícola, Jaboticabal, v.39, n.6, p.707-714, nov./dec. 2019 series (Dourado et al, 2013). Oliveira-Júnior et al (2017) reported that the identification of homogeneous zones was fundamental for agricultural planning.…”
Section: Introductionmentioning
confidence: 99%
“…The western part of the state of Bahia stands out in Brazil for good potential to produce eucalyptus, but the rainfall regime is very specific, with well-defined rainy and dry periods during the year, where the dry season on average lasts about five months (DOURADO et al, 2013). The municipality of Luis Eduardo Magalhães in western Bahia has climate and soil conditions similar to those elsewhere in Brazil where planted eucalyptus forests are extensive and highly productive.…”
Section: Introductionmentioning
confidence: 99%